2017
DOI: 10.1097/igc.0000000000001077
|View full text |Cite
|
Sign up to set email alerts
|

Fascin Is Associated With Aggressive Behavior and Poor Outcome in Uterine Carcinosarcoma

Abstract: Fascin is aberrantly expressed in both elements of UCS and is associated with aggressive behavior and worse outcome. As a component of EMT and mediator of invasion, fascin may serve as a target in future therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Nestin expression is observed in various embryonic cells and tissues, and a correlation of Nestin expression to clinical malignancy has been reported in melanoma and other tumors, such as breast cancer, ovarian cancer, and osteosarcoma [ 13 , 14 , 18 , 21 , 22 ]. Fascin, an actin-bundling protein, plays an important role in the regulation of cell adhesion, migration and invasion [ 23 , 24 , 25 , 26 , 27 ]. Fascin also exists in different tissues of the human body, such as mesenchyme and nervous tissue, however, it is not present in most normal epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…Nestin expression is observed in various embryonic cells and tissues, and a correlation of Nestin expression to clinical malignancy has been reported in melanoma and other tumors, such as breast cancer, ovarian cancer, and osteosarcoma [ 13 , 14 , 18 , 21 , 22 ]. Fascin, an actin-bundling protein, plays an important role in the regulation of cell adhesion, migration and invasion [ 23 , 24 , 25 , 26 , 27 ]. Fascin also exists in different tissues of the human body, such as mesenchyme and nervous tissue, however, it is not present in most normal epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…Here, an additional factor potentially related to recurrence has been added, specifically, Fascin-1 immunostaining. Fascin-1, an actin-bundling protein, plays an important role in the regulation of cell adhesion, migration, and invasion (27)(28)(29)35). Fascin-1 widely exists in different tissues of the human body, such as mesenchyme and nervous tissue, however it is not present in most normal epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…However, after 2019, Arlt et al reported Fascin-1 expression also correlates with progression and metastasis in osteosarcoma and chondrosarcoma ( 29 ). Additionally, Richmond et al reported that Fascin-1 is a mediator of invasion in uterine carcinosarcoma as a component of epithelial-mesenchymal transition ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported overexpression of FSCN1 in various gynecological cancers [ 123 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 ] as indicated in Table 1 .…”
Section: Fascin In Gynecological Cancersmentioning
confidence: 99%
“…Uterine carcinosarcoma cases were assessed for FSCN1 expression using IHC; while FSCN1 was absent in benign cases, it was present in both malignant epithelial and mesenchymal elements of uterine carcinosarcomas. This finding was associated with a more aggressive phenotype (advanced stage and large tumor size) and a poor outcome [ 142 ]. Additionally, FSCN1 was found to be a potential IHC biomarker in differentiating uterine leiomyosarcoma from leiomyoma [ 135 ].…”
Section: Fascin In Gynecological Cancersmentioning
confidence: 99%